DNA polymorphisms in inflammatory and endocrine signals linked to frailty are also associated with obesity: data from the FRASNET cohort - Damanti, Sarah; Citterio, Lorena; Zagato, Laura; Brioni, Elena; Magnaghi, Cristiano; Simonini, Marco; De Lorenzo, Rebecca; Ruggiero, Mariapia; Santoro, Simona; Senini, Eleonora; Messina, Marco; Vitali, Giordano; et al. (Frontiers in Endocrinology, 2024)
Background: Obesity and frailty are prevalent geriatric conditions that share some pathophysiological mechanisms and are associated with adverse clinical outcomes. The relationship between frailty, obesity, and polymorphism remains inadequately explored. Single nucleotide polymorphisms (SNPs) offer insights into genetic predispositions that may influence the development of both frailty and obesity.We aimed at investigating whether single nucleotide polymorphisms (SNPs) associated with frailty also play a role in obesity. Data were collected from the FRASNET cross-sectional study, which included community-dwelling older individuals residing in Milan and nearby areas. Participants were recruited through random sampling. They underwent multidimensional geriatric assessments, which included the collection of blood samples for single nucleotide polymorphism (SNP) analysis. Frailty was assessed using the frailty index, and body composition was evaluated using bioelectrical impedance analysis and anthropometric measures.Results: SNPs related to frailty and linked to the renin-angiotensin system (CYP11B2 rs1799998, AGT rs5051, AGTR1 rs2131127), apoptosis pathways (CASP8 rs6747918), growth hormone signaling (GHR rs6180), inflammation (TLR4 rs5030717, CD33 rs3865444, FN1 rs7567647), adducin (ADD3 rs3731566), and the 9p21-23 region (rs518054) were found to be associated with various measures of obesity in community-dwelling older adults.Frailty-related SNPs contribute to obesity in community-dwelling older adults. We identified a novel association between adducin SNPs and visceral fat, which has not been previously reported. Detecting genetic predispositions to obesity and frailty early could aid in identifying individuals at risk, facilitating the adoption of preventive interventions. This represents an initial step toward promoting early intervention strategies.